The heart of Spain : anthology of fiction, non-fiction, and poetry / Alvah Cecil Bessie - Bessie, Alvah Cecil (1904-1985) Álvarez del Vayo, Julio (1891-1975) Negrín, Juan (1892-1956)
Contiene textos de Julio Álvarez del Vayo y Juan Negrín